PHYLOGENY OF DREPANOSAURIDAE (REPTILIA: DIAPSIDA) - Senter P. (My University, 2004)
Phylogenetic analysis reveals that the Triassic diapsid family Drepanosauridae is closely related to Coelurosauravus and Longisquama. These three taxa are part of a clade for which the name Avicephala (defined as all taxa more closely related to Coelurosauravus and Megalancosaurus than to Neodiapsida) is coined. Avicephala is a sister taxon to Neodiapsida. The name Simiosauria is erected for the clade composed of all taxa more closely related to Drepanosauridae than to Coelurosauravus or Sauria. Simiosauria is composed of MCSNB 4751 + (Hypuronector + Drepanosauridae). Drepanosauridae is composed of Drepanosaurus + (Dolabrosaurus + Megalancosaurus). Arboreality is probably plesiomorphic for Avicephala and no convincing evidence exists that any simiosaurian was aquatic.
Keywords: DREPANOSAURIDAE; SIMIOSAURIA; AVICEPHALA; DIAPSIDA; COELUROSAURAVUS; LONGISQUAMA; MEGALANCOSAURUS; Triassic; Mesozoic::Triassic; Мезозой::Триасовая